Integrating Living Values and Educating Street Children to Fight for Mainstreaming: A Sociological Study in Dhaka City (Global Journal of Human-Social Science, 2018)
The street children who are known as the marginalized urban population in the developing countries, calls for mainstreaming or a social responsibility to engage actively with the prevention and change of the conditions that put these children at risk. This research paper is trying to find out what are the main phases to bring back our street children to the mainstream population along with proper care and nurture. It proposes working with services providers; supporting families and community participation; educating and forming alliance with public media; reforming legal and political framework; and empowering street children as the roles community psychologist can play in the mainstreaming process. It is further discussed that although these roles and strategies cannot be said to be the 'absolute antidote' to the street children phenomenon in Dhaka city, Bangladesh they can help to reduce the problem significantly. It is recommended that the concept of "small wins" should be adopted in the designing and implementation of intervention programs in order to overcome the plausible social, political, cultural and legal challenges that may arise in the process.
Keywords: street children; mainstream; education